Penerapan Pasal 138 Ayat (1) Kitab Undang-Undang Hukum Acara Pidana Terhadap Tindak Pidana Penelantaran Anak Di Kejaksaan Neger1 Kabupaten Probolinggo: (Studi Perkara Nomor: BP 1124 I XII / 2020 / Satreskrim) - Anton Suryadi; Devi Maharani (STIH Zainul Hasan Kraksaan Kraksaan, 2021)
In examining case files, the legal rule that is used as the basis is Article 138 paragraph (1) of the Criminal Procedure Code which provides provisions for prosecutors to immediately examine and examine case files after being submitted by investigators within a maximum deadline of 7 days. Each prosecutor's agency also has internal regulations for the maximum time limit for researching case files. The problems studied in this study and their objectives are first to find out the process of the Probolinggo District Attorney's Public Prosecutor in giving P21 to investigators in accordance with the provisions of Article 138 paragraph 1 of the Criminal Procedure Code. Second, to find out the factors that made the public prosecutor of the Probolinggo District Attorney's Office give P21 to investigators in the case file number: BP / 124 / XII 12020 / Satreskrim.Based on the formulation of the problem and the research objectives, the method used is an empirical juridical approach, namely legal research on the regulations governing case file research based on Article 138 Paragraph (1) of the Criminal Procedure Code associated with implementation in the Probolinggo District Attorney's Office. The results of research in the preparation of this thesis, firstly, the process of researching case files conducted by the public prosecutor at the Probolinggo District Prosecutor's Office was in accordance with the provisions of Article 138 paragraph 1 of the Criminal Procedure Code, and secondly the factors that made the District Attorney's Public Prosecutor Probolinggo gave P21 to investigators in the case file number: BP 1 124 / XII / 2020 I Satreskrim is based on the formal and material completeness of the case file.. Keyword: Implementation, Article 138 Paragraph (1) KUHAP, Case File Research